THE UNIQUENESS OF THE PATTERN, TYPE AND ENVIRONMENTAL SYSTEM OF CIHAPIT SETTLEMENT IN FACING THE DEVELOPMENT CHALLENGES IN BANDUNG CITY AREA: Kasus Studi Permukiman Cihapit Wilayah Cibeunying Kota Bandung - Chondro Kusumo, Irfan Febianto; R Tobing, Rumiati; Kusliansjah, Yohannes Karyadi (Ide dan Dialog Desain Indonesia (Idealog), 2023)
Changes in the physical order of an urban area are thought to occur due to economic development, changes in social aspects related to community behavior according to needs and lifestyles, and the carrying capacity of the environmental aspects where it is located. In reality, the development of urban areas runs spontaneously and so quickly, thus providing physical-spatial problems that can be encountered in everyday life. This research aims to identify the aspects that influence the occurrence of this phenomenon in the case study of the Cihapit Residential Neighborhood in Cibeunying area, Bandung City. The research was conducted through analyzing changes in physical-spatial elements that affect changes in the pattern, type and system of a case study area using the main approach of the study of Transformation and Permanence of Kostov's five Urban Form elements (Edge, Street, Subdivision, Buildings & Open space) in a qualitative diachronic manner based on the time context when the neighborhood was founded (1920s), its development period(1990s) and the present (2020s). The results of this study found things that were lost, survived and changed in the Pattern-Type-System relationship of the Urban Form element, and the disharmony of the physical spatial order of the multi-aspect Economic, Social and Environmental relationships. In addition, the permeability that occurs in the environment of the study object is suspected to be the main cause of Transformation and Function Change which results in changes in the scope of commercial services andphysical-spatial order problems in the Cihapit Settlement Environment in Bandung City. Keywords: Transformation, Permanence, Pattern-Type-System, Permeability, Cihapit Bandung City